Analysis of vehicle surge stimulated by accelerator pedal operation. (5th August 2014) - Kohno, T.; Morimoto, Y.; Igura, S.
A low–frequency fore–and–aft vibration of a vehicle stimulated by accelerator pedal operation was investigated by using a mathematical model simulating the drive train, suspension, sprung mass, seats and human body. As a result, it was found important to take into consideration the vehicle body behaviour in the model. The effect of each element was clarified and some counter–measures for the drive train and suspension were found. In addition, the effects of the input torque characteristics from the engine were investigated.